Inactivation of ancV1R as a Predictive Signature for the Loss of Vomeronasal System in Mammals. (21st April 2020) - Zhang, Zicong; Nikaido, Masato
Abstract: The vomeronasal organ (VNO) plays a key role in sensing pheromonal cues, which elicits social and reproductive behaviors. Although the VNO is highly conserved across mammals, it has been lost in some species that have evolved alternate sensing systems during diversification. In this study, we investigate a newly identified VNO-specific gene, ancV1R, in the extant 261 species of mammals to examine the correlation between genotype ( ancV1R ) and phenotype (VNO). As a result, we found signatures for the relaxation of purifying selection (inactivating mutations and the elevation of d N /d S ) on ancV1R s in VNO-lacking mammals, such as catarrhine primates, cetaceans, the manatees, and several bat lineages, showing the distinct correlation between genotype and phenotype. Interestingly, we further revealed signatures for the relaxation of purifying selection on ancV1R in true seals, otters, the fossa, the owl monkey, and alcelaphine antelopes in which the existence of a functional VNO is still under debate. Our additional analyses on TRPC2, another predictive marker gene for the functional VNO, showed a relaxation of purifying selection, supporting the possibility of VNO loss in these species. The results of our present study invite more in-depth neuroanatomical investigation in mammals for which VNO function remains equivocal.